IMPACT OF ROAD TRANSPORTATION ON AGRICULTURAL ACTIVITIES: PROBLEMS AND OPPORTUNITIES (British Journal of Global Ecology and Sustainable Development, 2024)
Road transport plays a crucial role in modern agricultural operations, facilitating the movement of materials, machinery and products. However, the increasing use of road transport in agriculture raises concerns about environmental sustainability, operational efficiency and economic efficiency. This article examines the impact of road transport on agricultural operations, highlights the challenges faced by farmers and explores opportunities for improving the transport system in agriculture.